DESIGNING AND TESTING SETS (SCIENCE, ENVIRONMENT, TECHNOLOGY AND SOCIETY) BASED MOTION COMIC INSTRUCTIONAL MEDIA ON ELECTROLYTE AND NON ELECTROLYTE SOLUTION - Rusdi Gunawan; Lazulva Lazulva (Universitas Negeri Surabaya, 2023)
This research was instigated by the lack of instructional media variation used in the learning process. This research aimed at knowing the levels of validity and practicality of SETS (Science, Environment, Technology, and Society) based Motion Comic instructional media on Electrolyte and non-Electrolyte Solution lesson. It was R&D (Research and Development) with 4- D (Devine, Design, Development, Disseminate) model. It was administered at State Senior High School 02 Siak Hulu. The data were primary, the data were obtained directly from questionnaire. The obtained data were analysed by using qualitative and quantitative descriptive analysis techniques. SETS based Motion Comic video media developed was tested valid with 95.7% percentage (very valid) and practical with 90.71% percentage (very practical). Based on these findings, it could be concluded that SETS based Motion Comic video media on Electrolyte and non- Electrolyte Solution lesson was valid and practical, so it could be done the limited trials.